Rate of Cornea Endothelial Cell Loss and Biomechanical Properties in Fuchs' Endothelial Corneal Dystrophy - Reinprayoon, Usanee; Jermjutitham, Monthira; Kasetsuwan, Ngamjit (Frontiers in Medicine, 2021)
Background: Our study aimed to determine the correlation between the clinical staging of Fuchs’ endothelial corneal dystrophy (FECD), rate of endothelial cell loss, and corneal biomechanical properties. Methods: This study combined a longitudinal retrospective/prospective analysis of corneal endothelial cell loss and a prospective cross-sectional analysis of corneal biomechanics of Fuchs’ endothelial dystrophy. The trial was registered at the Thai Clinical Trials Registry as TCTR 20160927004. FECD was diagnosed by the presence of corneal guttata detected by slit lamp microscopy; the disease severity was classified into four stages using the modified Stocker’s classification. In vivo confocal microscopy, Scheimpflug imaging, and Corneal Visualization Scheimpflug Technology were performed to evaluate endothelial cell count, central corneal thickness, and corneal biomechanical properties. Linear mixed modeling analyses were used to estimate the endothelial cell densities in a 4-year period. The corneal biomechanics were compared among the stages using Corvis ST parameters. Results: Eighty eyes from eighty subjects were enrolled (42, 26, 12, and none in stages 1, 2, 3, and 4, respectively). The mean endothelial cell density was 1228.35 cells/mm2. The year-by-year reduction rate was 94.3 cells/mm2 (µEMM = -94.3, 95%CI: -115.4 to -73.2, p < 0.001). Corneal endothelial cell losses in Fuchs’ endothelial dystrophy were estimated to be 7.7%, 7.8%, and 8.4% per year for stages 1, 2, and 3, respectively. The mean corneal thicknesses of stages 1, 2, and 3 were 556 ± 32 mm, 623 ± 33 mm, and 648 ± 50 mm, respectively. For the corneal biomechanical parameters, the A1-length and A1-time were significantly different between stages 1 and 3 (A1-length: mean diffstage1vs3 = 0.10, 95%CI: <0.001 to 0.15, p < 0.001, A1-time: mean diffstage1vs3 = -0.24, 95%CI: -0.41 to -0.07, respectively). Conclusions: In the advanced stage, corneas significantly changed their biomechanical viscoelastic behavior by decreasing resistance, as measured by a longer A1-length and shorter A1-time.